MODELING OF WATER CIRCULATION IN THE ANTARCTIC SUBGLACIAL LAKE VOSTOK - G. Kazko V.; L. Savatyugin M.; I. Sokratova N.; Г. Казко В.; Л. Саватюгин М.; И. Сократова Н. (Ice and Snow, 2015)
Different ways of defining the characteristics of Antarctic subglacialLakeVostokcirculation are considered. The disadvantages of hydrodynamic models using the hydrostatic approximation exposed to analysis. Differential equations and boundary conditions of three-dimensional nonhydrostatic model in terms vorticity–vector potential, specially developed for the modelling of the lake circulation are presented. 3D model passed through the testing by means simulations of convective currents in the simple-form reservoirs. On the basis of the seismic data on the thickness of a glacier and bathimetry of the lake the computational domain approximating a water body ofLakeVostokis constructed. Some results of modeling of the convective processes in the lake, obtained at the initial stage of circulation evolution using finite-difference grid with a spatial resolution of 8000 × 1500 ×30 mare shown. Рассматриваются разные способы определения характеристик циркуляции озера Восток. Анализируются недостатки гидродинамических моделей, использующих гидростатическое приближение. Приводятся уравнения и граничные условия численной трёхмерной негидростатической модели в переменных завихрённость – векторный потенциал, специально разработанной для расчёта циркуляции озера. Показаны результаты моделирования начального этапа развития конвективной циркуляции озера в предположении, что в момент начала численного эксперимента вода в озере находилась в состоянии покоя.